2019
DOI: 10.11604/pamj.2019.33.246.19341
|View full text |Cite
|
Sign up to set email alerts
|

A case of squamous cell carcinoma occurring on a scar of Buruli ulcer in Bouake, Ivory Cost

Abstract: Buruli ulcer is infectious necrotizing panniculitis due to Mycobacterium ulcerans. Buruli ulcer is healed by leaving dystrophic, fibrous and retractile scars. On these scars can occur long-term squamous cell carcinoma. We report the first case of squamous cell carcinoma occurring on healing of Buruli ulcer. A 32-year-old woman with Buruli ulcer who has been cured for about 10 years is seen for ulcero-bulging knee swelling. The examination had revealed a large swelling of about ten centimeters in diameter, ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Additionally, it is assumed that sun exposure could play a significant role in squamous carcinoma growth in individuals with fair skin like our patient; however, other factors that result in chronic ulcers like infectious, discoid lupus erythematosus, and HIV infection could be responsible in the individuals with darker skin. 6 Generally, these Marjolin ulcers have been categorized into acute and chronic types depending on the time period between the first injury and the malignancy appearance on the injured skin. A recent investigation revealed that the average duration for this process is approximately 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it is assumed that sun exposure could play a significant role in squamous carcinoma growth in individuals with fair skin like our patient; however, other factors that result in chronic ulcers like infectious, discoid lupus erythematosus, and HIV infection could be responsible in the individuals with darker skin. 6 Generally, these Marjolin ulcers have been categorized into acute and chronic types depending on the time period between the first injury and the malignancy appearance on the injured skin. A recent investigation revealed that the average duration for this process is approximately 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…1 The pathogenesis of these chronic types could be related to the ongoing insults and irritations to the scar tissue associated with the lack of vascularization, resulting in decreasing the local immunity of the area and the tumor growth. 6 F I G U R E 1 An ulcerated nodule on the middle line of the chest, exactly in the middle of his sternotomy scar, with 3-cm diameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scarring can lead to disfigurement, impaired mobility, and reduced elasticity making it more prone to cracking and injuries 76 . A rare complication is the development of squamous cell carcinoma at scar site 85,86 .…”
Section: Clinical Featuresmentioning
confidence: 99%